GABA and glutamate neurons in the VTA regulate sleep and wakefulness - Yu,X; Li,W; Ma,Y; Tossell,K; Harris,J; Harding,E; Ba,W; Miracca,G; Wang,D; Li,L; Guo,J; Chen,M; et al. (Nature Neuroscience, 2019)
We screened for novel circuits in the mouse brain that promote wakefulness. Chemogenetic activation experiments and electroencephalogram recordings pointed to glutamatergic/nitrergic (NOS1) and GABAergic neurons in the ventral tegmental area (VTA). Activating glutamatergic/NOS1 neurons, which were wake- and rapid eye movement (REM) sleep-active, produced wakefulness through projections to the nucleus accumbens and the lateral hypothalamus. Lesioning the glutamate cells impaired the consolidation of wakefulness. By contrast, activation of GABAergic VTA neurons elicited long-lasting non-rapid-eye-movement-like sleep resembling sedation. Lesioning these neurons produced an increase in wakefulness that persisted for at least 4 months. Surprisingly, these VTA GABAergic neurons were wake- and REM sleep-active. We suggest that GABAergic VTA neurons may limit wakefulness by inhibiting the arousal-promoting VTA glutamatergic and/or dopaminergic neurons and through projections to the lateral hypothalamus. Thus, in addition to its contribution to goal- and reward-directed behaviors, the VTA has a role in regulating sleep and wakefulness.